Acute effects of mechanical dyssynchrony on left ventricular function and coronary perfusion - Choy, Jenny S.; Fan, Lei; Awakeem, Yousif; Cai, Chenghan; Raissi, Farshad; Lee, Lik Chuan; Kassab, Ghassan S. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundPatients with heart failure frequently develop mechanical dyssynchrony, which impairs ventricular function, coronary perfusion and their interactions. The underlying mechanisms, however, remain poorly understood due to numerous confounding factors. The objective of this study was to determine the acute effects of mechanical dyssynchrony on global and regional left ventricular (LV) function, coronary perfusion and their interactions based on experimental and computational approaches.MethodsMechanical dyssynchrony was created with right ventricular apical pacing in Yorkshire domestic swine (n = 9). The heart was paced at 100 and 140 bpm and the results were compared to right atrial pacing. An inverse finite element computational framework based on an animal-specific geometry of the LV and measurements was developed to investigate the effects of mechanical dyssynchrony on LV function and its correlation with regional coronary perfusion.ResultsCardiac dyssynchrony induced significant decrease in LV pressure, volume, dP/dt(min), stroke volume, ejection fraction, and regional longitudinal and circumferential strain. With mechanical dyssynchrony, passive flow decreased by 70% in the left anterior descending artery (LAD) and 67% in the left circumflex (LCX). An animal-specific inverse finite element computational model predicted that in mechanical dyssynchrony, global and regional LV contractility in the septum and LV free wall (LVFW), and myocardial work done in the septum and LVFW decreased.ConclusionThe computational model predicted reduction in global and regional contractility, and regional myocardial work done in the septum and LVFW with mechanical dyssynchrony are positively correlated with the corresponding decrease in experimentally measured regulated coronary flow in the LAD and LCX. These findings demonstrate that this interrelated mechanism between LV function and coronary flow in mechanical dyssynchrony may affect cardiac resynchronization therapy responder rate.